De novo biosynthesis of the late endosome lipid, bis(monoacylglycero)phosphates - Hullin-Matsuda, Françoise; Kawasaki, Kiyoshi; Delton-Vandenbroucke, Isabelle; Xu, Yang; Nishijima, Masahiro; Lagarde, Michel; Schlame, Michael; Kobayashi, Toshihide (Journal of lipid research, 2007)
Bis(monoacylglycero)phosphate (BMP) is a unique lipid enriched in the late endosomes participating in the trafficking of lipids and proteins through this organelle. The de novo biosynthesis of BMP has not been clearly demonstrated. We investigated whether phosphatidylglycerol (PG) and cardiolipin (CL) could serve as precursors of de novo BMP synthesis using two different cellular models: CHO cells deficient in phosphatidylglycerophosphate (PGP) synthase, the enzyme responsible for the first step of PG synthesis; and human lymphoblasts from patients with Barth syndrome (BTHS), characterized by mutations in tafazzin, an enzyme implicated in the deacylation-reacylation cycle of CL. The biosynthesis of both PG and BMP was reduced significantly in the PGP synthase-deficient CHO mutants. Furthermore, overexpression of PGP synthase in the deficient mutants induced an increase of BMP biosynthesis. In contrast to CHO mutants, BMP biosynthesis and its fatty acid composition were not altered in BTHS lymphoblasts. Our results thus suggest that in mammalian cells, PG, but not CL, is a precursor of the de novo biosynthesis of BMP. Despite the decrease of de novo synthesis, the cellular content of BMP remained unchanged in CHO mutants, suggesting that other pathway(s) than de novo biosynthesis are also used for BMP synthesis.